Longitudinal assessment of mercury exposure in schoolchildren in an urban area of the Brazilian Amazon Avaliação longitudinal da exposição ao mercúrio em crianças de uma área urbana na Amazônia brasileira - Marilene Danieli Simões Dutra; Iracina Maura de Jesus; Elisabeth C. de Oliveira Santos; Marcelo de Oliveira Lima; Renato Lopes Fernandes de Medeiros; Marcia Cavadas; Ronir Raggio Luiz; Volney de Magalhães Câmara (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This study was a longitudinal assessment of mercury exposure in schoolchildren in an urban area of the Brazilian Amazon. The study population consisted of 90 children whose exposure levels were assessed by testing mercury levels in the umbilical cord blood and mothers' blood samples in 2000-2001, and in the children's hair and blood samples. The study also used a questionnaire on demographic and socioeconomic data, fish consumption, and self-reported disease history. Mean mercury level in hair in 2010 was approximately 1µg/g, ranging up to 8.22µg/g, similar to 2004 and 2006. These figures can be explained by low fish consumption. Mean blood mercury levels at birth exceeded 10µg/L, ranging up to nearly 60µg/L, which indicates mercury transfer across the placenta. There was a significant increase in blood mercury from 2004 to 2006 (p < 0.001), suggesting exposure through air pollution. The main exposure to mercury was during pregnancy. O objetivo deste estudo foi realizar avaliação longitudinal da exposição de crianças de uma área urbana da Amazônia brasileira ao mercúrio (Hg). A população foi composta por 90 crianças, cuja exposição foi avaliada desde o nascimento por meio das análises dos teores de Hg no sangue do cordão umbilical e no sangue das mães em 2000/2001, e em amostras de cabelo e sangue das crianças. Os procedimentos incluíram também um questionário com informações demográficas, socioeconômicas, sobre consumo de peixes e morbidade referida. A média dos teores de Hg no cabelo em 2010 foi próxima a 1µg/g e sua amplitude 8,22µg/g, semelhantes aos anos 2004 e 2006, podendo ser explicada pela baixa ingestão de peixes. A média dos teores de Hg no sangue das crianças ao nascer ultrapassou 10µg/L e sua amplitude atingiu quase 60µg/L, indicando transferência do Hg através da barreira placentária. Ocorreu aumento significativo dos teores de Hg no sangue entre 2004 e 2006 (p < 0,001), sugerindo a possibilidade de exposição atmosférica ao Hg. O principal período de exposição ao Hg ocorreu durante a gestação.